Multiple choice test examination in the university - Berestova, Anna V.; Romanova, Marina V.; Tatiana N. Shurukhina, Denis A. Klyuchnikov,; Nuretdinova, Yuliya V. (Opción, 2019)
The goal of research is to determine the attitude and stress level of students during multiple-choice tests. To achieve the goal, we conducted a poll among students of five Russian universities. The study used the quantitative research methodology to collect and analyze the values of the poll. As a result, those who tend to worry about exams were also less susceptible to distraction when searching for goals. In conclusion, students, generally have a positive attitude towards multiple-choice tests, despite mentioning some disadvantages that may influence test objectivity.